2016
DOI: 10.20883/jms.2016.117
|View full text |Cite
|
Sign up to set email alerts
|

Delivering bad news by physicians – Polish reality check

Abstract: Introduction. Disclosing unfavorable information is a very important moment in both diagnostic and therapeutic processes. It is also a highly stress‑inducing factor, both among patients and physicians. During our research we tried to establish how exactly bad news is communicated to patients and the amount of stress that Polish physicians are under in such situations.Material and Methods. Quantitative research was conducted in a university clinical hospital. With the use of an anonymous questionnaire, physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
(2 reference statements)
0
9
0
2
Order By: Relevance
“… 16 , 17 These results support the findings gathered in our earlier studies in which a larger number of patients than doctors expressed their need for partnership and open communication in clinical relationships that will enable them to participate in the process of decision-making as regards their further medical therapy and to fully realize the patient’s right to access all the information about their health. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 These results support the findings gathered in our earlier studies in which a larger number of patients than doctors expressed their need for partnership and open communication in clinical relationships that will enable them to participate in the process of decision-making as regards their further medical therapy and to fully realize the patient’s right to access all the information about their health. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies indicated that there are two main factors that escalate doctors’ stress level in the process of DBN. 8 , 9 The first of these factors is the education gap in terms of soft skills, which is present in the process of education of medical university students in Poland. The second factor is paternalistic viewpoint among doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies by other researchers indicated that there are two integral factors that increase doctors' stress in the process of dispersing BDN which are deficits in education in terms of the soft skills required and the paternalistic approach of medical doctors. 9,10 Our research indicated some patients would like to receive their diagnostic news from medium other than medical doctors, although the statistics varied depending on their perceived health status (sick or healthy). Another question that arises from our research is how equipped these other media are in delivering BDN.…”
Section: Introductionmentioning
confidence: 90%
“…Dwoma głównymi czynnikami zwiększającymi poziom stresu wśród lekarzy w czasie przekazywania złych informacji są brak zdobycia tzw. umiejętności miękkich w czasie studiów oraz utrzymujący się nadal paternalistyczny stosunek lekarzy do pacjentów [19,20]. Wykazano, iż uczestnictwo w Areopagu Etycznym istotnie wpłynęło na przewidywania dotyczące nasilenia niektórych odczuć, które mogą towarzyszyć przekazywaniu trudnej informacji pacjentowi: zmniejszyły się m.in.…”
Section: Dyskusjaunclassified